Three‐Dimensional Computed Tomographic Analysis of Normal and Aneurysmal Aortic Roots: Is There a Specific Geometric Pattern in the Aortic Root? - Ju, Min Ho; Oh, Sang Young; Choo, Suk Jung; Yang, Dong Hyun; Kang, Joon‐Won; Kim, Joon Bum; Shinn, Sung Ho; Lee, Jae Won; Lim, Tae‐Hwan (Clinical anatomy (New York, N.Y.), 2020)
Current knowledge of the aortic root geometric anatomy and its surgical implications remain limited. We analyzed multiple predefined parameters of the aortic root to increase our understanding of the geometric changes that occur in normal and aneurysmal transformations. Between November 2003 and September 2015, the aortic roots of 107 healthy subjects (control group) and 105 annuloaortic ectasia (AAE) patients (AAE group) were analyzed using multiplanar reformatted computed tomographic images. The intercommissural distance (ICD), sinus width (SW), and sinus volume (SV) of the left (LCS), right (RCS), and noncoronary sinuses (NCS) of Valsalva were adopted as study parameters. In the control group, all study parameters of the LCS were smaller than those of the RCS and the NCS. In the AAE group, all parameters of the LCS were significantly smaller than those of the RCS or NCS, but the RCS and NCS parameters were similar. Proportionately less LCS enlargement relative to either the RCS or NCS was observed in root aneurysm(AAE group) than in the control group. We observed a distinct aortic root geometric pattern which was characterized by the LCS being smaller than either the RCS or NCS, while the latter were similar. This geometric configuration was significantly accentuated in AAE patients due to the greater disproportionate disparity in the LCS relative to either the RCS or NCS than in the roots of normal control subjects. Clin. Anat. 32:117–123, 2019. © 2019 Wiley Periodicals, Inc.